High-efficiency promoter-driven coordinated regulation of multiple metabolic nodes elevates lipid accumulation in the model microalga Phaeodactylum tricornutum - Li-Gong Zou; Jia-Wen Chen; Dan-Lin Zheng; Srinivasan Balamurugan; Da-Wei Li; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Microbial Cell Factories, 2018)
Abstract Background Microalgal metabolic engineering holds great promise for the overproduction of a wide range of commercial bioproducts. It demands simultaneous manipulation of multiple metabolic nodes. However, high-efficiency promoters have been lacking. Results Here we report a strong constitutive promoter Pt211 in expressing multiple target genes in oleaginous microalga Phaeodactylum tricornutum. Pt211 was revealed to contain significant cis-acting elements. GUS reporter and principal genes glycerol-3-phosphate acyltransferase (GPAT) and diacylglycerol acyltransferase 2 (DGAT2) involved in triacylglycerol biosynthesis were tested under driven of Pt211 in P. tricornutum. GUS staining and qPCR analysis showed strong GUS expression. DGAT2 and GPAT linked with a designed 2A sequence exhibited higher transcript abundances than WT, while algal growth and photosynthesis were not impaired. Conclusion The total lipid content increased notably by 2.6-fold compared to WT and reached up to 57.5% (dry cell weight). Overall, our findings report a strong promoter and a strategy for coordinated manipulation of complex metabolic pathways.